The Effectiveness of Mentalization-Based Treatment on Alexithymia and Internalizing Behavioral Problems in Adolescents of Divorce - Youzbashi, Maryam; Ghorban Shiroudi, Shohreh; Jadidi, Mohsen (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: The present study aimed to investigate the effectiveness of mentalization-based treatment on alexithymia and internalizing behavioral problems in adolescents of divorce. Methods and Materials: This applied research was quasi-experimental with a pretest-posttest design, a control group, and a two-month follow-up period. The statistical population consisted of adolescents of divorce in the first secondary school stage of Education District 14 in Tehran during the academic year 2022-2023. In this study, 36 adolescents of divorce were selected using purposive sampling and randomly assigned to experimental (19 participants) and control (17 participants) groups. The experimental group received mentalization-based treatment over eight weeks in 8 sessions of 90 minutes each. The questionnaires used in this study included the Alexithymia Questionnaire (AQ) and the Child and Adolescent Behavior Inventory (CABI). The data obtained from the research were analyzed using mixed analysis of variance with SPSS23 statistical software. Findings: The results indicated that mentalization-based treatment had a significant impact on alexithymia (P<0.0001; Eta=0.61; F=52.83) and internalizing behavioral problems (P<0.0001; Eta=0.59; F=48.48) in adolescents of divorce. Conclusion: Based on the research findings, it can be concluded that mentalization-based treatment, by employing thoughts, emotions, and behaviors associated with mindfulness, can be used as an effective method to reduce alexithymia and internalizing behavioral problems in adolescents of divorce.